Humanin, a Mitochondrial-Derived Peptide Released by Astrocytes, Prevents Synapse Loss in Hippocampal Neurons - Zárate, Sandra Cristina; Traetta, Marianela Evelyn; Codagnone, Martín Gabriel; Seilicovich, Adriana; Reinés, Analía Gabriela (Frontiers in Aging Neuroscience, 2019)
Astroglial cells are crucial for central nervous system homeostasis. They undergo complex morpho-functional changes during aging and in response to hormonal milieu. Ovarian hormones positively affect different astroglia parameters, including regulation of cell morphology and release of neurotrophic and neuroprotective factors. Thus, ovarian hormone loss during menopause has profound impact in astroglial pathophysilogy and has been widely associated to the process of brain aging. Humanin is a secreted mitochondrial-encoded peptide with neuroprotective effects. It has been localized in several tissues with high metabolic rate and its expression decreases with age. In the brain, humanin has been localized in glial cells in physiological conditions. We previously reported that surgical menopause induces hippocampal mitochondrial dysfunction that mimics an aging phenotype. However, the effect of ovarian hormone deprivation on humanin expression in this area has not been studied. Also, whether astrocytes express and release humanin and the regulation of such processes by ovarian hormones remain elusive. Although humanin has also proven to be beneficial in ameliorating cognitive impairment induced by different insults, its putative actions on structural synaptic plasticity have not been fully addressed. In a model of surgical menopause in rats, we studied hippocampal humanin expression and localization by RT-qPCR and double immunohistochemistry, respectively. Humanin production and release and ovarian hormone regulation of such processes were studied in cultured astrocytes by flow cytometry and ELISA, respectively. Humanin effects on glutamate-induced structural synaptic alterations were determined in primary cultures of hippocampal neurons by immunocytochemistry. Humanin expression was lower in the hippocampus of ovariectomized rats and its immunoreactivity colocalized with astroglial markers. Chronic ovariectomy also promoted the presence of less complex astrocytes in this area. Ovarian hormones increased humanin intracellular content and release by cultured astrocytes. Humanin prevented glutamateinduced dendritic atrophy and reduction in puncta number and total puncta area for presynaptic marker synaptophysin in cultured hippocampal neurons. In conclusion, astroglial functional and morphological alterations induced by chronic ovariectomy resemble an aging phenotype and could affect astroglial support to neuronal function by altering synaptic connectivity and functionality. Reduced astroglial-derived humanin may represent an underlying mechanism for synaptic dysfunction and cognitive decline after menopause.